Identifying Conversational Structures and Strategies between Guide and Foreign Guests in Transactional Negotiation of Tour (Transport) Service - Irsan Hambali (Universitas Muhammadiyah Mataram, 2018)
This article aimed to find conversational structure and strategies employed by guides in transactional negotiation with foreign guests and find out the best one, which latter becomes standardized conversational structures and strategies in persuading and satisfying customers. This paper examined structures of conversation with regard to Sinclair-Coulthard’s Birmingham model. This study is qualitative in nature, attempting to describe data, represented in the form of words. During data collection, utterances were recorded directly by a set of tape-recorders then transcribed into spoken text. Later, the recorded data were analyzed using Sinclair Coulthard analysis model of within or outside classroom discourse. The data were analyzed in terms of the four discourse units: transaction, exchange, move, and acts. Among these four units, exchange and move were mainly focused. The result showed that the structure of guides’ conversation in doing transactional negotiation is somewhat the same. Starting from so – called starter which consist of question and answer then transaction which employed question and informing and the last is closing. There were 3 scripts epitomized the result. The script 1 and 2 merely focused on price without explaining the itinerary and car services extensively. The script 3 showed the success of transaction, that is how guide employed strategic communication in transactional negotiation.